The Implementation of Eclectic Methods in Arabic Learning Based on All in One System Approach - Wahidah, Zulfa Amalia; Baroroh, Umi; Mukadam, Abdur Rasheed-Mahmoud (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
Each method has different function and characteristic. One method is not enough to achieve four language skills in Arabic language learning.  We need a method that is able to accommodate the weaknesses of the previous method. This research aimed to examine the implementation of eclectic method based on all in one system approach. This method integrates the various methods in language teaching and achieves four language skills. This research provided a new model to implementation the methods, specifically eclectic method and their connection with Arabic language skills. The method used in this research was qualitative method based on text analysis. The data research was collected from sources of books, journal articles, or matters relating to the topic of this study. The result of this research was the use of an eclectic method based on all in one system approach (integrated approach) which can facilitate Arabic language teaching. A language teacher needs to consider this method for students. This research also examined the various aspects and how they could be useful for teacher in Arabic language classroom.  The study provided further support for the use of eclectic method for student in mastering four Arabic language skills.